MARGARET THATCHER’S STRUGGLES AGAINST WOMEN SUBORDINATION REPRESENTED IN “THE IRON LADY” MOVIE - ACINTA, - - (Jurnal Ilmiah Mahasiswa FIB, 2014)
Subordination of women always happens in a patriarchal society.Patriarchy is a system by the power of men which always regard women as beingweak. This results in unfairness to women's rights. Women often become objectsthat are humiliated and harassed, the actions they do were always limited. Theimpact of this injustice makes some women move to fight subordination of them.This phenomenon is reflected in one of the biography film "The Iron Lady" thatelevates the struggle of a woman to be a leader in a world dominated by men. The study aims at revealing the struggle of Margaret Thatcher against thesubordination of women that is reflected in the film. The writer examines Margaret Thatcher's oppression and struggle throughthe lens of feminism that focuses on women's issues, one of which is due to thepatriarchal system. The elements of mise-en-scene in the film was alsoimplemented to see other forms of oppression and the struggle associated with the arrangement of setting, costume, lighting, and other elements. From the analysis, it is known that because of the patriarchal system that isformed by society, women must experience gender discrimination. However, "TheIron Lady" indicates that there are contra actions of women to gain genderequality as shown by Margaret Thatcher, as the main character, in which she triedto fight for her rights. They are included getting higher education, making her own decision, becoming a strong leader, and also involving and politics. To achieve her dream as a career woman, she managed to break the low assumption about women that are weak, ignorant, and passive. The writer would like to give some suggestion for the next researchers.First, next researchers need to conduct further research on the analysis reveals the important things in it, because this film can still be analyzed by using the other theory of literature, such as capitalism. It would be an interesting study for the next researchers that can be observed the difference in social status between the bourgeoisie and the proletariat can affect the right to be a leader.. The second possibility is then can use the same theory that is feminism for other materials.Hopefully researchers will next get a different conclusion using the same theory. Keywords: Struggle, subordination, feminism, The Iron Lady.